The Liturgical Targum : The Aramaic Translation of the Torah in Mahzorim - Verrijssen, Jeroen, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
What happens when a community continues to recite and transmit sacred texts it no longer understands? The Targum, or Aramaic translation of the Hebrew Bible, found its origins in the first centuries CE, and yet Jewish communities continued to transmit its contents well into the Middle Ages, when knowledge of Aramaic was considered to be scarce. This book explores the Liturgical Targum as it appears in festival prayerbooks (mahzorim). Drawing on previously unpublished manuscript fragments, it traces how different Jewish communities adopted and adapted the Aramaic translation in their liturgies. You'll discover how layers of copying, and reinterpretation, and scribal creativity shaped the textual history of the Targum.